Synthesis of Water Soluble C-10-Phenoxy Artemisinin-Chitosan Conjugate - Xiao, Dan; Yang, Bo; Chen, Yun-Jian; Liao, Xia-Li; Yang, Xue-Min; Qin, Qi-Xue; Yi, Dong (Asian Journal of Chemistry, 2013)
A sort of C-10-phenoxy artemisinin-chitosan conjugate, in which C-10-phenoxy artemisinin was covalently bound to chitosan, was prepared and its aqueous solubility was evaluated. The results indicated that the conjugate (1.013 mg/mL) had much higher aqueous solubility than artemisinin (0.0084 mg/mL) and C-10-phenoxy artemisinin (0.0245 mg/mL). The conjugate will be potentially useful for their application as the prodrug of artemisinin.